A Variance-Ratio Test of Random Walks in Foreign Exchange Rates. - He, Jia; Liu, Christina Y (Journal of Finance, 1991)
The separate variance-ratio tests under homoscedasticity and heteroscedasticity both provide evidence rejecting the random walk hypothesis using five pairs of weekly nominal exchange rate series over the period from August 7, 1974, to March 29, 1989. The rejections cast doubt on the random walk hypothesis in exchange rates, which has received support in the existing literature. Furthermore, since the rejections are robust to heteroscedasticity, they suggest autocorrelations of weekly increments in the nominal exchange rate series, which may be consistent with the exchange rate overshooting or undershooting phenomenon.